Alzheimer's disease: the "microbial hypothesis" from a clinical and neuroimaging perspective - Frölich, Lutz (Psychiatry research. Neuroimaging, 2020)
The etiology of Alzheimer's disease (AD) is under debate since its first description in 1906. Extracellular senile plaques composed of beta-amyloid peptide (Aβ) and intracellular neurofibrillary tangles composed of tau protein characterize the histopathology of the disease. The ‘amyloid cascade hypothesis’ summarizes the molecular mechanisms leading to deposition of these proteins. However, treatments derived from this hypothesis have been unsuccessful. An infectious etiology for AD has been repeatedly proposed. Neurotropic viruses, gut and lung bacteriae, and Bovine Meat and Milk Factors have been implicated in neurodegenerative disorders including AD. These pathogens may act directly or as a trigger or co-factor for inducing neurodegeneration in AD. The antimicrobial properties of beta-amyloid have shifted the discussion of the etiological origin of AD towards an interaction hypothesis. Neuroimaging studies have added to the understanding of mechanisms involved in neurodegeneration. Antiviral agents and a bacterial protease inhibitor targeting Porphyromonas gingivalis toxins are currently tested in clinical trials. Further clinical studies are needed to test if strategies directly derived from the ‘microbial hypothesis’ or combination strategies including antimicrobial agents may be beneficial for patients with Alzheimer's disease.